The role of pharmacies in the implementation of vaccination coverage in Italy. Insights from the preliminary data of the Lombardy Region - Pennisi, Flavia; Mastrangelo, Marco; De Ponti, Emanuele; Cuciniello, Rita; Mandelli, Andrea; Vaia, Francesco; Signorelli, Carlo (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Introduction. The administration of vaccines in pharmacies was not allowed in Italy until 2021. During the COVID-19 pandemic, legislative innovations were introduced that now allow qualified pharmacists to administer anti-flu and anti-COVID-19 vaccines after completing specific training. Methods. The article provides an overview of legislation concerning vaccinations in Italian pharmacies, followed by a description of the vaccinations carried out by pharmacies participating in the regional vaccination campaign from 2021 to 2023. The study relies on data extracted from the Lombardy Region’s database on vaccine administration in pharmacies. Furthermore, innovative vaccination practices from the Marche Region were also taken into consideration. Study Design. Observational Study Results. Lombardy became the Italian pioneer region in extensively incorporating pharmacy-based vaccinations, starting in 2021. This initiative reached its zenith with 46% of anti-COVID vaccines and 17% of flu vaccines administered within the first six weeks of the autumn 2023 campaign. Pharmacies played a crucial role in meeting the targets outlined in the Italian National Vaccine Prevention Plan for 2023-25. As part of an experimental program, the Marche Region has further expanded pharmacy-based vaccinations, now including anti-zoster and anti-pneumococcus vaccines for the 2023-24 campaign. Conclusions. The promising outcomes observed in Lombardy and the ongoing experimental efforts in the Marche are encouraging steps toward achieving vaccination coverage targets, albeit still falling below the objectives set by the National Vaccination Plan for 2023-25. The widespread presence of pharmacies throughout the territory makes them well-suited as support structures for vaccination campaigns, especially in reaching the adult, the elderly, and the vulnerable populations.